2019
DOI: 10.1093/ije/dyz122
|View full text |Cite
|
Sign up to set email alerts
|

Compared with whom? Reference groups in socio-economic comparisons and self-reported health in 34 countries

Abstract: Background The association between socio-economic position and health is believed to be mediated, in part, by psycho-social comparison of one’s situation with that of others. But with whom? Possibilities include family, friends, elites, or even those in other countries or in previous times. So far, there has been almost no research on whether the reference point matters. Methods We take advantage of a comparative data set tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…According to this approach individuals differ by the type of groups or individuals they choose as a reference for comparison and the nature of actual comparisons they make with the selected groups of individuals (Buunk and Gibbons, 2007). It is known that when asked to select a benchmark for socio-economic comparison of their current socio-economic conditions, about one-fifth of individuals compare themselves with their own parents (Gugushvili, Jarosz, et al, 2019). One reason for this is that children unconsciously internalise not only parental values and behaviours but also the socio-economic environment in which they were growing up (Bandura, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…According to this approach individuals differ by the type of groups or individuals they choose as a reference for comparison and the nature of actual comparisons they make with the selected groups of individuals (Buunk and Gibbons, 2007). It is known that when asked to select a benchmark for socio-economic comparison of their current socio-economic conditions, about one-fifth of individuals compare themselves with their own parents (Gugushvili, Jarosz, et al, 2019). One reason for this is that children unconsciously internalise not only parental values and behaviours but also the socio-economic environment in which they were growing up (Bandura, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…The first, “Generally speaking, how would you assess your health in comparison with the health of most people at your age?” has five answer options ranging from “definitely better” to “definitely worse.” This question is different from a more conventional self-rated health question as it contains an element of comparison to others, and should consequently be interpreted accordingly. Earlier research suggests that social comparison to family members, friends, neighbors, and other more distant groups (e.g., those learned about in the media) is an important implication for individuals’ health and wellbeing ( Gugushvili et al, 2019a ; Gugushvili and Reeves, 2021 ). The second question asks: “How would you assess your own psychological wellbeing?…”
Section: Methodsmentioning
confidence: 99%
“…We analyse data from the Life in Transition Survey (LITS) collected in 2016 by the European Bank for Reconstruction and Development (EBRD) [ 26 ], from 34 countries in Europe, the Middle East, and Central Asia (list of countries and sociodemographic composition of samples is given in Table S1 in the supplementary materials). LITS has been recently used in comparative health and wellbeing research [ 27 29 ], including in studies on individuals’ anthropometric measures and their effects on wellbeing [ 30 , 31 ]. LITS ensures the national representativeness of the collected data by using a multi-stage random probability stratified clustered sampling.…”
Section: Methodsmentioning
confidence: 99%
“…However, research on how the effect of BMI on LS is shaped by the social context is limited and the evidence is mixed. Small sample studies have reported no association between one's own weight and obesity rates among the social comparison reference group members [25]. Conversely, some large-scale studies suggest that in areas with high levels of BMI, the negative effect of obesity on LS is weaker, and that this association differs by gender [17].…”
Section: Introductionmentioning
confidence: 99%